Frauen am Bauhaus : Wegweisende Künstlerinnen der Moderne - Rössler, Patrick; Otto, Elizabeth (München : Knesebeck Verlag, 2019)
Dicker, Friedl ; Friedlaender-Wildenhain, Marguerite ; Grunow, Gertrud ; Stölzl, Gunta ; Driesch-Foucar, Lydia ; Fehling, Ilse ; Heymann-Loebenstein, Margarete ; Koch-Otte, Benita ; Scheper-Berkenkamp, Lou ; Leudesdorff-Engstfeld, Lore ; Soupault, Ré ; Albers, Anni ; Arndt, Gertrud ; Moholy, Lucia ; Gropius, Ise ; Bayer, Irene ; Beyer-Volger, Lis ; Brandt, Marianne ; Hollós-Consemüller, Ruth ; Both, Katt ; Meyer-Bergner, Lena ; Reichardt, Margaretha ; Berger, Otti ; Dambeck, Margarete ; Henri, Florence ; Kallin-Fischer, Grit ; Leischner, Margarete ; Meyer-Waldeck, Wera ; Stam-Beese, Lotte ; Mittag-Fodor, Etel ; Grosch, Karla ; Leiteritz, Margaret ; Tudor-Hart, Edith ; Tomljenović, Ivana ; Ullmann-Broner, Monica Bella ; van der Mijll Dekker, Kitty Fischer ; Bánki, Zsuzska ; Schwerin, Ricarda ; Stern, Grete ; Yamawaki, Michiko ; Blühová, Irena ; Kárász, Judit ; Hubbuch, Hilde ; Steyn, Stella ; Reich, Lilly
boek